Managing Cash Flow and Financial Efficiency in Logistics Companies: Analyzing Practices and Their Impacts - Lovita, Erna; Prabantoro, Gatot; Roswida, Karisma Devi (Labkat Press KA FTIK UNIKOM, 2024)
The phenomenon shows that the performance of the freight transport industry in Indonesia must be intensified to be more competitive, facing the current era of e-commerce technology-based business. This study examines the understanding and practices of cash flow management at PT. SMI Cargo and their impact on the company's financial efficiency. Through interviews with management and financial data analysis, PT was found. SMI Cargo places significant emphasis on cash flow management as a key indicator of financial health. Interactive analysis was employed as the primary methodology, which involves four stages: data collection, reduction, presentation, and conclusion drawing. This approach allowed for a systematic examination of cash flow practices, uncovering key insights into the company’s financial strategies. Data triangulation was used to enhance the validity and credibility of the research findings. The company enforces strict controls over expenditures and receivables collection to maintain cash flow stability—routine assessments of financial reports and financing effectiveness aid strategic decision-making. The company may create successful business strategies, such as pricing and promotional efforts, as well as PT, using accurate financial records and careful data analysis. For asset and revenue management, SMI Cargo has a strong internal control system in place that guarantees asset values are always correct and current. Compared to the prior period, net cash flow grew by up to 40% as a result of cost control and improved client payments. Investor interest is piqued and sustained financial performance is supported by this simple yet efficient financial management. This study did not thoroughly examine external elements that could affect the company's financial performance, such as macroeconomic conditions and regulatory changes in the logistics industry. To give a more complete picture of the company's financial performance, more study must take into account the in-depth investigation of external issues, such as macroeconomic conditions, regulatory changes, or trends in the logistics market.